Trabalhando com textos no ensino superior - Magda Floriana Damiani (Universidade do Minho, 2008)
This paper has the objective of presenting, discussing and evaluating a teaching activity proposal for the undergraduate level. Such proposal is based mainly on reading and discussing texts, demanding an active posture on the part of students. It has been developed as an alternative to traditional pedagogical activities which usually use texts as mere sources of information. The proposal is supported by Socio-Historic Psychology and has been implemented at the Federal University of Pelotas (Brazil). It was analyzed through written evaluations that contained the opinions of Pedagogy students about it. The evaluations underwent a process of thematic analysis and indicated that the proposal, in spite of some criticism (related mainly to the effort necessary to develop the assigned tasks), has been considered successful. The students reported that, through the activities they have carried out, they were able to: understand the texts in a more profound manner and internalize their content more efficiently; establish interconnections with other information previously learned and/or life experiences; and reflect upon what they have learned. They also reported developing and improving their written expression abilities and other abilities related to thinking processes